Method for manufacturing connector and adhesive film

By using a binder film of dendritic conductive particles and conductive layer conductive particles, the appearance and resistance problems in the connection of concave and convex electrodes are solved, and excellent connector performance and bubble suppression effect are achieved, which are suitable for high-temperature and low-temperature conditions.

CN114746524BActive Publication Date: 2024-12-24RESONAC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080083968.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2020-12-03
Publication Date
2024-12-24
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

When an electronic component with an uneven surface and an electrode is provided in the recessed portion is connected to a flat electrode, it is difficult for the conventional adhesive to obtain a connector with excellent appearance and low resistance, especially in the recessed portion, air bubbles are easily generated, which affects the performance of the connector.

Method used

By using a binder film containing conductive particles and conductive layer conductive particles provided on a non-conductive nucleus, the second electronic component with a substantially flat surface electrode is electrically connected to the first electronic component with a concave and convex surface, the second electronic component with a substantially flat surface is electrically connected to the first electronic component with a concave and convex surface. The thickness of the adhesive film and the average particle size of the conductive particles are used to optimize the appearance and resistance characteristics of the connector.

Benefits of technology

A connection body with excellent appearance and low resistance is achieved in the concave-convex electrode connection, suppresses the generation of air bubbles in the recess, and maintains resistance stability under high or low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114746524B_ABST
    Figure CN114746524B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a connector, which includes a step of electrically connecting a second electronic component having a second electrode to a first electronic component having a first electrode via an adhesive film, wherein the first electronic component has a concave-convex surface, the first electrode is arranged in a concave portion of the concave-convex surface, the second electrode is an electrode having a substantially flat surface whose area is larger than that of the first electrode, the adhesive film contains: a first conductive particle which is a dendritic conductive particle; and a second conductive particle which is a conductive particle other than the first conductive particle and is a conductive particle having a non-conductive core and a conductive layer arranged on the core, the average particle size of the second conductive particle being greater than the depth of the concave portion, and in the above step, the adhesive film is arranged between the first electronic component and the second electronic component, and the second electronic component is crimped to the first electronic component in such a way that the substantially flat surface of the second electrode is electrically connected to the first electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a connector and an adhesive film. Background Art

[0002] In recent years, various adhesives have been used to fix electronic devices and connect circuits in the fields of semiconductors and liquid crystal displays. In these applications, electronic components such as electronic devices and circuits are becoming more and more dense and sophisticated, and adhesives are also required to have higher levels of performance. In addition, since the structure of a suitable adhesive can be changed depending on the electronic component to be connected, it is necessary to study adhesives in consideration of the structure and characteristics of the electronic components.

[0003] For example, in Patent Document 1, an anisotropic conductive adhesive is disclosed for the purpose of providing a manufacturing method of a connector and an anisotropic conductive adhesive, wherein the connector uses an anisotropic conductive adhesive that not only ensures conductivity for electrode terminals having an oxide film formed on the surface, but also has insulation between adjacent wirings, and the anisotropic conductive adhesive comprises: a binder resin; a first conductive adhesive layer having first conductive particles dispersed in the binder resin; and a second conductive adhesive layer stacked on one surface of the first conductive adhesive layer, and second conductive particles having a particle size smaller than that of the first conductive particles are dispersed in the binder resin.

[0004] Previous technical literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-182823 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] An object of the present invention is to obtain a connection body with excellent appearance and low resistance when an electronic component having flat electrodes is connected to an electronic component having irregularities on its surface and electrodes provided in the recesses of the irregularities.

[0009] Means for solving technical problems

[0010] According to the research of the inventors, when connecting an electronic component having uneven surfaces and electrodes provided in the concave parts of the uneven surfaces to an electronic component having flat electrodes, not all adhesives are suitable for connection. In order to solve the above-mentioned problem, that is, to obtain a connection body with excellent appearance (specifically, to suppress the generation of bubbles in the concave parts) and low resistance, a specific adhesive needs to be used. In addition, the appearance and resistance of the connection body here refer to the appearance and resistance as the so-called initial characteristics just after the connection body is obtained.

[0011] One aspect of the present invention is a method for manufacturing a connector, which includes a step of electrically connecting a second electronic component having a second electrode to a first electronic component having a first electrode via an adhesive film, wherein the first electronic component has a concave-convex surface, the first electrode is arranged in a concave portion of the concave-convex surface, the second electrode is an electrode having a substantially flat surface whose area is larger than that of the first electrode, the adhesive film contains: a first conductive particle, which is a dendritic conductive particle; and a second conductive particle, which is a conductive particle other than the first conductive particle and is a conductive particle having a non-conductive core and a conductive layer arranged on the core, the average particle size of the second conductive particle being greater than the depth of the concave portion. In the above step, the adhesive film is arranged between the first electronic component and the second electronic component, and the second electronic component is crimped to the first electronic component in such a way that the substantially flat surface of the second electrode is electrically connected to the first electrode.

[0012] Another aspect of the present invention is an adhesive film, which contains: a first conductive particle, which is a dendritic conductive particle; and a second conductive particle, which is a conductive particle other than the first conductive particle, and is a conductive particle having a non-conductive core and a conductive layer arranged on the core, the adhesive film is used for electrically connecting a first electronic component having a first electrode and a second electronic component having a second electrode, the first electronic component having a concave-convex surface, the first electrode being arranged in a concave portion of the concave-convex surface, the average particle size of the second conductive particle being greater than the depth of the concave portion, the second electrode being an electrode having a substantially flat surface whose area is larger than the area of ​​the first electrode, and in the electrical connection, the substantially flat surface of the second electrode is electrically connected to the first electrode.

[0013] The thickness of the adhesive film may be 15 μm or more. The thickness of the adhesive film may be greater than the depth of the recess. The average particle size of the second conductive particles may be less than 2.5 times the depth of the recess. The thickness of the adhesive film may be greater than 1.2 times and less than 2.0 times the average particle size of the second conductive particles.

[0014] Effects of the Invention

[0015] According to the present invention, when an electronic component having flat electrodes is connected to an electronic component having irregularities on its surface and electrodes provided in the recessed portions of the irregularities, a connection body having excellent appearance and low resistance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic cross-sectional view showing one embodiment of a method for producing a connected body.

[0017] Figure 2 It is a figure for demonstrating the evaluation method of appearance in Example.

[0018] Figure 3 It is a diagram for explaining the method of measuring the resistance in Examples. DETAILED DESCRIPTION

[0019] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings, depending on the circumstances. In addition, unless otherwise specified, the materials exemplified below may be used alone or in combination of two or more. In the case where there are a variety of substances equivalent to each component in the composition, unless otherwise specified, the content of each component in the composition refers to the total amount of the various substances present in the composition. In addition, the numerical range represented by "~" represents the range in which the numerical values ​​recorded before and after "~" are included as the minimum and maximum values, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage may be replaced by the upper limit or lower limit of the numerical range of another stage. In addition, in the numerical range recorded in this specification, the upper limit or lower limit of the numerical range may be replaced by the value shown in the embodiment. In addition, the upper limit and lower limit recorded separately may be arbitrarily combined. In addition, "A or B" may include any one of A and B, or both.

[0020] One embodiment of the present invention is a method for producing a connected body, including a step of electrically connecting a second electronic component to a first electronic component via an adhesive film (connection step). Figure 1 Schematic cross-sectional view showing one embodiment of a method for manufacturing a connected body. Figure 1 As shown, in this manufacturing method, first, a first electronic component 1, a second electronic component 2, and an adhesive film 3 are prepared.

[0021] The first electronic component 1 includes a first substrate 4, an insulating layer 5 provided on one surface of the first substrate 4, and a first electrode 6. The surface of the first electronic component 1 (the surface on the side connected to the second electronic component 2) is formed into a concave-convex shape by the insulating layer 5. That is, in the first electronic component 1, a plurality of insulating layers 5 provided in a convex shape on the first substrate 4 constitute a convex portion 1a, and these plurality of insulating layers 5 are provided separately from each other, so that the gaps between the plurality of insulating layers 5 constitute a concave portion 1b. The first electrode 6 is provided in the concave portion 1b on the first substrate 4.

[0022] The length L1 of the recess 1b (the length in the direction parallel to the surface of the first substrate 4 on which the insulating layer 5 and the first electrode 6 are provided) can be, for example, 25 μm or more, or 3 mm or less. The depth D of the recess 1b (the distance from the surface of the first electrode 6 to the upper surface of the insulating layer 5) can be, for example, 5 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, or 25 μm or more, or 40 μm or less.

[0023] The first substrate 4 may be, for example, a substrate formed of glass, ceramic, polyimide, polycarbonate, polyester, polyethersulfone, etc. The insulating layer 5 may be, for example, a layer formed of a solder resist or a cover film. The first electrode 6 may be, for example, an electrode formed of gold, silver, copper, tin, aluminum, ruthenium, rhodium, palladium, osmium, iridium, platinum, indium tin oxide (ITO), etc. The thickness of the first electrode 6 may be, for example, 5 μm or more, 10 μm or more, or 20 μm or less, 100 μm or less, or 50 μm or less.

[0024] The second electronic component 2 includes a second substrate 7 and a second electrode 8 provided on one surface of the second substrate 7. The second substrate 7 may be, for example, a substrate formed of polyimide, polycarbonate, polyester, polyethersulfone, etc. The second electrode 8 may be an electrode formed of gold, silver, copper, tin, aluminum, ruthenium, rhodium, palladium, osmium, iridium, platinum, indium tin oxide (ITO), etc. The thickness of the second electrode 8 may be, for example, 5 μm or more, 10 μm or more, or 20 μm or less, 100 μm or less, or 50 μm or less.

[0025] The second electrode 8 has a substantially flat surface 8a. The area of ​​the substantially flat surface 8a of the second electrode 8 is larger than the area of ​​the first electrode 6. That is, the length L2 of the substantially flat surface 8a of the second electrode 8 (the length in a direction parallel to the surface of the second substrate 7 on which the second electrode 8 is provided) is longer than the length L1 of the first electrode 6.

[0026] In one embodiment, the adhesive film 3 is composed of an adhesive layer including an adhesive component 9 and first conductive particles 10 and second conductive particles 11 dispersed in the adhesive component 9 .

[0027] The adhesive component 9 is composed of a material that is curable by heat or light, for example, and may be an epoxy adhesive, a free radical curing adhesive, a thermoplastic adhesive containing polyurethane and polyvinyl ester, etc. The adhesive component 9 may be composed of a cross-linking material because of its excellent heat resistance and moisture resistance after bonding. The epoxy adhesive contains a thermosetting resin, i.e., epoxy resin, as a main component. From the viewpoints of being able to cure in a short time, having good connection operability, and having excellent adhesion, the adhesive component 9 may be an epoxy adhesive. Compared with the epoxy adhesive, the free radical curing adhesive has the characteristics of being more excellent in curability at low temperature and in a short time, so it can be appropriately used according to the application.

[0028] The epoxy adhesive contains, for example, an epoxy resin (thermosetting material) and a curing agent, and may contain a thermoplastic resin, a coupling agent, a filler, and the like as necessary.

[0029] As epoxy resin, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, bisphenol F novolac type epoxy resin, alicyclic epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, hydantoin type epoxy resin, isocyanurate type epoxy resin, aliphatic chain epoxy resin, etc. can be cited. These epoxy resins can be halogenated, hydrogenated, or have a structure in which an acryloyl group or a methacryloyl group is added to a side chain. These epoxy resins can be used alone or in combination of two or more.

[0030] The curing agent is not particularly limited as long as it can cure the epoxy resin, and examples thereof include anionic polymerization catalyst-type curing agents, cationic polymerization catalyst-type curing agents, and addition-type curing agents. Among them, anionic or cationic polymerization catalyst-type curing agents may be used from the viewpoint of excellent rapid curing properties and no need to consider chemical equivalents.

[0031] Examples of anionic or cationic polymerizable catalyst-type curing agents include imidazoles, hydrazides, boron trifluoride-amine complexes, onium salts (aromatic sulfonium salts, aromatic diazonium salts, aliphatic sulfonium salts, etc.), aminoimides, diaminomaleonitrile, melamine and its derivatives, polyamine salts, dicyandiamide, etc., and modified products thereof can also be used. Examples of polyaddition-type curing agents include polyamines, polythiols, polyphenols, acid anhydrides, etc.

[0032] From the viewpoint of being able to extend the usable time, these curing agents may be latent curing agents that are microencapsulated by polymers such as polyurethane and polyester, metal films such as nickel and copper, inorganic substances such as calcium silicate, etc. The curing agents may be used alone or in combination of two or more.

[0033] The content of the curing agent may be 0.05 to 20 parts by mass based on 100 parts by mass of the total amount of the thermosetting material and the thermoplastic resin blended as needed.

[0034] The radical curing adhesive contains, for example, a radical polymerizable material and a radical polymerization initiator (also referred to as a curing agent), and may further contain a thermoplastic resin, a coupling agent, a filler, and the like as necessary.

[0035] As free radical polymerizable materials, for example, any material having a functional group that polymerizes by free radicals can be used without particular limitation. Specifically, free radical polymerizable materials such as acrylate compounds (including corresponding methacrylates, the same below), acryloxy compounds (including corresponding methacryloyloxy groups, the same below), maleimide compounds, citraconimide resins, and nadiimide resins can be cited. These free radical polymerizable materials can be in the form of monomers or oligomers, or in the form of a mixture of monomers and oligomers.

[0036] Examples of the acrylate compound include methacrylate, ethyl acrylate, isopropyl acrylate, isobutyl acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane triacrylate, tetramethylolmethane tetraacrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxypolyethoxy)phenyl]propane, dicyclopentyl acrylate, tricyclodecyl acrylate, tris(acryloxyethyl)isocyanurate, urethane acrylate, and phosphate diacrylate.

[0037] As required, free radical polymerizable materials such as acrylate compounds may be used together with polymerization inhibitors such as hydroquinone and methyl ether hydroquinone. From the viewpoint of improving heat resistance, free radical polymerizable materials such as acrylate compounds may have at least one substituent such as dicyclopentenyl, tricyclodecyl, triazine ring, etc. Free radical polymerizable materials other than acrylate compounds may be, for example, compounds described in International Publication No. 2009 / 063827. Free radical polymerizable materials may be used alone or in combination of two or more.

[0038] As the radical polymerization initiator, any compound that decomposes and generates free radicals by heating or light irradiation can be used without particular limitation. Specifically, for example, peroxide compounds, azo compounds, etc. can be cited. These compounds are appropriately selected according to the target connection temperature, connection time, pot life, etc.

[0039] As the radical polymerization initiator, more specifically, diacyl peroxide, peroxydicarbonate, peroxyester, peroxyketal, dialkyl peroxide, hydroperoxide, silyl peroxide etc. can be enumerated. The radical polymerization initiator can be peroxyester, dialkyl peroxide, hydroperoxide, silyl peroxide etc., and can be peroxyester from the viewpoint of obtaining high reactivity. These radical polymerization initiators, for example, can be the compound recorded in International Publication No. 2009 / 063827. The radical polymerization initiator can be used alone or in combination of two or more.

[0040] The content of the radical polymerization initiator may be 0.1 parts by mass or more, or 10 parts by mass or less, based on 100 parts by mass of the total amount of the radical polymerizable material and the thermoplastic resin blended as necessary.

[0041] In epoxy adhesives and free radical curing adhesives, the thermoplastic resins prepared as needed are, for example, easy to form the adhesive into a film. As thermoplastic resins, for example, phenoxy resins, polyvinyl formal resins, polystyrene resins, polyvinyl butyral resins, polyester resins, polyamide resins, xylene resins, polyurethane resins, polyester urethane resins, phenolic resins, terpene phenolic resins, etc. can be cited. Thermoplastic resins can be, for example, compounds described in International Publication No. 2009 / 063827. Thermoplastic resins can be phenoxy resins because of their excellent adhesion, compatibility, heat resistance, mechanical strength, etc. Thermoplastic resins can be used alone or in combination of two or more.

[0042] When mixed with epoxy adhesive, the content of thermoplastic resin can be 5 parts by mass or more, or 80 parts by mass or less, relative to 100 parts by mass of the total amount of thermoplastic resin and thermosetting material. When mixed with radical curing adhesive, the content of thermoplastic resin can be 5 parts by mass or more, or 80 parts by mass or less, relative to 100 parts by mass of the total amount of thermoplastic resin and radical polymerizable material.

[0043] As another example of the adhesive component 9, a thermal radical curing adhesive can be cited, which contains a thermoplastic resin, a radical polymerizable material that is liquid at 30° C., and a radical polymerization initiator. Compared with the above-mentioned adhesives, the thermal radical curing adhesive has a low viscosity. The content of the radical polymerizable material in the thermal radical curing adhesive may be 20 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more, or 80 parts by mass or less, relative to 100 parts by mass of the total amount of the thermoplastic resin and the radical polymerizable material.

[0044] The adhesive component 9 may be an epoxy adhesive containing a thermoplastic resin, a thermosetting material containing an epoxy resin that is liquid at 30° C., and a curing agent. In this case, the content of the epoxy resin in the epoxy adhesive may be 20 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more, or 80 parts by mass or less, relative to 100 parts by mass of the total amount of the thermoplastic resin and the thermosetting material.

[0045] The content of the adhesive component 9 in the adhesive film 3 (the volume ratio of the adhesive component 9 in the adhesive film 3) can be, for example, 55% by volume or more or 65% by volume or less, or 95% by volume or less or 85% by volume or less based on the total volume of the adhesive film 3.

[0046] The first conductive particle 10 is dendritic (also called dendrite-like) and has a main axis and a plurality of branches branching from the main axis two-dimensionally or three-dimensionally. The first conductive particle 10 may be made of a metal such as copper or silver, and may be a silver-coated copper particle in which a copper particle is coated with silver.

[0047] The first conductive particles 10 may be known conductive particles, and specifically, may be obtained as ACBY-2 (MITSUI MINING & SMELTING CO., LTD.), CE-1110 (UKUDA METAL FOIL & POWDER Co., Ltd.), #FSP (JX Nippon Mining & Metals Corporation), #51-R (JX Nippon Mining & Metals Corporation), etc. Alternatively, the first conductive particles 10 may be produced by a known method (for example, the method described in International Publication No. 2014 / 021037).

[0048] From the viewpoint of further reducing the resistance of the connector, the content of the first conductive particles 10 in the adhesive film 3 can be greater than 5 volume %, greater than 6 volume %, greater than 7 volume %, greater than 8 volume %, greater than 9 volume %, or greater than 10 volume % based on the total volume of the adhesive film 3. From the viewpoint of improving the adhesion of the adhesive film, the content can be less than 30 volume %, less than 25 volume %, less than 22 volume %, less than 20 volume %, less than 18 volume %, or less than 15 volume %.

[0049] The second conductive particle 11 has a non-conductive core and a conductive layer disposed on the core. The core is formed of a non-conductive material such as glass, ceramic, resin, and can be formed of a resin. As the resin, for example, acrylic resin, styrene resin, silicon copper resin, polybutadiene resin or a copolymer of monomers constituting these resins can be cited. The average particle size of the core can be appropriately selected so that the average particle size of the second conductive particle 11 is within the range described below.

[0050] The conductive layer is formed of, for example, gold, silver, copper, nickel, palladium, or an alloy thereof. From the viewpoint of excellent conductivity, the conductive layer may contain at least one selected from gold, nickel, and palladium, may contain gold or palladium, and may further contain gold. The conductive layer is formed, for example, by plating the above metals on the core body. The thickness of the conductive layer may be, for example, not less than 10 nm, or not more than 400 nm.

[0051] The average particle size of the second conductive particles 11 may be 10 μm or more or 20 μm or more. From the viewpoint of being able to properly form a conductive path in the recess 1b of the first electronic component 1 and suppressing the deterioration of the appearance and resistance value even when the connector is placed at a high or low temperature, the average particle size may be 25 μm or more, 27 μm or more, or 30 μm or more. From the viewpoint of being able to properly thin the adhesive film 3, the average particle size of the second conductive particles 11 may be 50 μm or less, 40 μm or less, or 30 μm or less. The average particle size of the second conductive particles 11 and the core bodies constituting the second conductive particles 11 is measured by a particle size distribution measuring device (Microtrac (product name, Nikkiso Co., Ltd.)) using a laser diffraction / scattering method.

[0052] From the viewpoint of obtaining a connector having excellent appearance and low resistance, the average particle size of the second conductive particles 11 is greater than the depth D of the recess 1b. From the viewpoint of more easily obtaining this effect, it may be greater than 1.1 times or greater than 1.2 times the depth D of the recess 1b. The average particle size of the second conductive particles 11 may be greater than 5 μm, greater than 10 μm, or greater than 20 μm. The average particle size of the second conductive particles 11 may be less than 100 μm, less than 60 μm, or less than 60 μm. From the viewpoint of obtaining a connector having excellent appearance and low resistance, it may be less than 2.5 times, less than 2.0 times, less than 1.7 times, less than 1.5 times, less than 1.4 times, less than 1.3 times, or less than 1.2 times the depth D of the recess 1b.

[0053] The content of the second conductive particles 11 in the adhesive film 3 (the volume ratio of the second conductive particles 11 in the adhesive film 3) can be greater than 1 volume %, greater than 2 volume %, greater than 3 volume %, greater than 5 volume %, less than 20 volume %, less than 10 volume %, less than 8 volume %, or less than 5 volume % based on the total volume of the adhesive film 3.

[0054] From the viewpoint that the recess 1b in the first electronic component 1 can be appropriately filled with the adhesive component 9 and the like, and that the appearance and resistance value can be prevented from being deteriorated even when the connected body is placed at high or low temperatures, the thickness of the adhesive film 3 can be 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, or 40 μm or more. From the same viewpoint, the thickness of the adhesive film 3 can be greater than the depth D of the recess 1b, or 1.1 times or 1.2 times the depth D of the recess 1b or more.

[0055] The thickness of the adhesive film 3 may be, for example, 70 μm or less, 60 μm or less, or 50 μm or less. The thickness of the adhesive film 3 may be, for example, 2.5 times or less, 2.0 times or less, 1.7 times or less, or 1.5 times or less the depth D of the recess 1 b.

[0056] From the viewpoint of making it easier to obtain a connector with excellent appearance and low resistance, and of suppressing degradation of appearance and resistance even when the connector is placed at high or low temperatures, the thickness of the adhesive film 3 can be greater than 1.0 times, greater than 1.1 times, or greater than 1.2 times the average particle size of the second conductive particles, or less than 2.0 times, less than 1.8 times, less than 1.6 times, less than 1.5 times, less than 1.4 times, or less than 1.3 times the average particle size of the second conductive particles.

[0057] In the connection step, the adhesive film 3 is arranged between the first electronic component 1 and the second electronic component 2, and the second electronic component 2 is pressed and bonded to the first electronic component 1. Specifically, the substantially flat surface 8a of the second electrode 8 is electrically connected to the first electrode 6. Figure 1 The second electronic component 2 is pressurized and heated in the direction of the arrow X (the stacking direction of the first electronic component 1, the adhesive film 3, and the second electronic component 2). The heating temperature can be, for example, 50° C. or more, or 190° C. or less. The pressure can be, for example, 0.1 MPa or 30 MPa. The time for performing these heating and pressurizing can be, for example, 0.5 seconds or more, or 120 seconds or less.

[0058] As described above, a method for manufacturing a connector according to one embodiment includes a step of electrically connecting a second electronic component having a second electrode to a first electronic component having a first electrode via an adhesive film, wherein the first electronic component has a concave-convex surface, the first electrode is arranged in a concave portion of the concave-convex surface, the second electrode is an electrode having a substantially flat surface whose area is larger than that of the first electrode, the adhesive film contains: a first conductive particle, which is a dendritic conductive particle; and a second conductive particle, which is a conductive particle other than the first conductive particle and is a conductive particle having a non-conductive core and a conductive layer arranged on the core, the average particle size of the second conductive particle being greater than the depth of the concave portion, and in the step, the adhesive film is arranged between the first electronic component and the second electronic component, and the second electronic component is crimped to the first electronic component in such a way that the substantially flat surface of the second electrode is electrically connected to the first electrode.

[0059] Furthermore, an adhesive film involved in one embodiment contains: a first conductive particle, which is a dendritic conductive particle; and a second conductive particle, which is a conductive particle other than the first conductive particle, and is a conductive particle having a non-conductive core and a conductive layer arranged on the core. The adhesive film is used for electrically connecting a first electronic component having a first electrode and a second electronic component having a second electrode. The first electronic component has a concave-convex surface, and the first electrode is arranged in a concave portion of the concave-convex surface. The average particle size of the second conductive particle is greater than the depth of the concave portion. The second electrode is an electrode having a substantially flat surface whose area is larger than the area of ​​the first electrode. In the electrical connection, the substantially flat surface of the second electrode is electrically connected to the first electrode.

[0060] A connection body is obtained by the above manufacturing method. The connection body comprises: a first electronic component 1 having a first substrate 4, an insulating layer 5 provided on the first substrate 4, and a first electrode 6; a second electronic component 2 having a second substrate 7 and a second electrode 8 provided on the second substrate 7; and a connection member for electrically connecting the first electrode 6 and the second electrode 8 to each other. The connection member comprises a cured product of an adhesive component 9 and first conductive particles 10 and second conductive particles 11 dispersed in the cured product. That is, the connection member is formed by curing the above-mentioned adhesive film 3.

[0061] Example

[0062] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to the following examples.

[0063] (Preparation of adhesive solution)

[0064] 50 g of a phenoxy resin (manufactured by Union Carbide Corporation, product name: PKHC, weight average molecular weight: 45,000) was dissolved in a mixed solvent of toluene (boiling point: 110.6° C.) and acetic acid (boiling point: 77.1° C.) (mass ratio of toluene:acetic acid = 1:1) to obtain a phenoxy resin solution having a solid content of 40% by mass. In the phenoxy resin solution, urethane acrylate (manufactured by Negami Chemical Industrial Co., Ltd., product name: UN7700) and dimethyl phosphate acrylate (manufactured by KYOEISHA CHEMICAL CO., LTD., product name: LIGHT ESTER P-2M) as free radical polymerizable materials and 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane (manufactured by NOFCORPORATION, product name: PERHEXA TMH) as a curing agent are mixed in a solid mass ratio of phenoxy resin:urethane acrylate:dimethyl phosphate acrylate:curing agent = 10:10:3:2 to obtain an adhesive solution.

[0065] (First conductive particle)

[0066] As the first conductive particles, dendritic conductive particles (silver-coated copper particles, manufactured by MITSUI MINING & SMELTING CO., LTD., product name: ACBY-2) were used.

[0067] (Preparation of Second Conductive Particle a)

[0068] First, benzoyl peroxide as a polymerization initiator is added to a mixed solution of divinylbenzene, styrene monomer and butyl methacrylate, and the mixture is heated while being uniformly stirred at a high speed to carry out a polymerization reaction, thereby obtaining a microparticle dispersion. The microparticle dispersion is filtered and dried under reduced pressure to obtain a block as a microparticle aggregate. In addition, a core body (resin particle) is produced by crushing the block.

[0069] Next, a palladium catalyst (manufactured by MUROMACHI TECHNOS CO., LTD., product name: MK-2605) is loaded on the surface of the above-mentioned core body, and the core body activated by a promoter (manufactured by MUROMACHI TECHNOS CO., LTD., product name: MK-370) is added to a mixed solution of an aqueous nickel sulfate solution, an aqueous sodium hypophosphite solution, and an aqueous sodium tartrate solution heated to 60°C, and an electroless plating pre-process is performed. The mixture is stirred for 20 minutes, and it is confirmed that the bubbling of hydrogen stops. Next, a mixed solution of nickel sulfate, sodium hypophosphite, sodium citrate, and a plating stabilizer is added, stirred until the pH is stable, and an electroless plating post-process is performed until the bubbling of hydrogen stops. Next, the plating solution is filtered, and after washing the filtrate with water, it is dried in a vacuum dryer at 80°C to produce a second conductive particle a plated with nickel. The average particle size of the second conductive particle a is 30 μm, and the thickness of the conductive layer is 150 nm.

[0070] (Preparation of Second Conductive Particles b)

[0071] Second conductive particles b were obtained in the same manner as the second conductive particles a except that the particle size of the core body was changed. The second conductive particles b had an average particle size of 20 μm and a conductive layer thickness of 100 nm.

[0072] (Preparation of Second Conductive Particles c)

[0073] Second conductive particles c were obtained in the same manner as the second conductive particles a except that the particle size of the core body was changed. The second conductive particles c had an average particle size of 10 μm and a conductive layer thickness of 100 nm.

[0074] (Preparation of Second Conductive Particles d)

[0075] Second conductive particles d were obtained in the same manner as the second conductive particles a except that the particle size of the core body was changed. The second conductive particles d had an average particle size of 40 μm and a conductive layer thickness of 100 nm.

[0076] (Preparation of Second Conductive Particles e)

[0077] Second conductive particles e were obtained in the same manner as the second conductive particles a except that the particle size of the core body was changed. The second conductive particles e had an average particle size of 60 μm and a conductive layer thickness of 100 nm.

[0078] <Adhesive film production>

[0079] A mixed solution was obtained by dispersing the first conductive particles and the second conductive particles in the above-mentioned adhesive solution so that the contents of the first conductive particles and the second conductive particles in the obtained adhesive film were the amounts shown in Table 1. The obtained mixed solution was applied to a fluororesin film having a thickness of 80 μm, and the solvent was removed by hot air drying at 70° C. for 10 minutes, thereby obtaining adhesive films of the thickness shown in Table 1 formed on the fluororesin film.

[0080] The following evaluations were performed using each adhesive film. The results are shown in Table 1.

[0081] [Evaluation of initial characteristics]

[0082] <Appearance>

[0083] Make as Figure 2 The appearance evaluation sample 20 shown. Figure 2 (a) is a top view of the sample 20 for appearance evaluation, Figure 2 (b) is along Figure 2 (a) is a cross-sectional view along line IIb-IIb.

[0084] Specifically, first, any one of the polyimide films 22 of different thicknesses (size: 25mm×25mm, thickness: 10μm, 20μm, 25μm, 35μm or 50μm) is placed on a glass slide 21 (size: 26mm×76mm, thickness: 1mm). In addition, a slit (recess) 22a (size: 20mm×0.5mm, depth: 10μm, 20μm, 25μm, 35μm or 50μm) is formed in the approximate center of the polyimide film 22. Next, an aluminum foil 24 (size: 15mm×20mm, thickness: 25μm) is connected to the polyimide film 22 via each of the adhesive films 23 (size: 15mm×3mm) obtained above.

[0085] Each of the obtained appearance evaluation samples 20 was observed from the slide glass 21 side (towards Figure 2 The inside of the slit 22a of the polyimide film 22 was observed with an optical microscope (in the field of view where the entire slit 22a can be observed) to confirm the presence or absence of bubbles in the slit 22a. The appearance was evaluated as follows based on the presence or absence (number) of bubbles larger than 50 μm. If the evaluation was A or B, it can be said that the appearance is excellent.

[0086] A: No bubbles larger than φ50μm

[0087] B: The number of bubbles larger than φ50μm is 1 to 2

[0088] C: The number of bubbles larger than φ50μm is 3 or more

[0089] <Resistance>

[0090] Make as Figure 3 The resistance measurement sample 30 is shown. Figure 3 (a) is a top view of the resistance measurement sample 30, Figure 3 (b) is along Figure 3 (a) is a cross-sectional view along line IIIb-IIIb.

[0091] Specifically, first, any one of the polyimide films 22 of different thicknesses (size: 25 mm × 25 mm, thickness: 10 μm, 20 μm, 25 μm, 35 μm or 50 μm) is placed on the copper foil 31 (size: 35 mm × 35 mm, thickness: 25 μm). In addition, a slit 32a (size: 20 mm × 0.5 mm, depth: 10 μm, 20 μm, 25 μm, 35 μm or 50 μm) is formed in the approximate center of the polyimide film 32. Next, an aluminum foil 34 (size: 15 mm × 20 mm, thickness: 25 μm) is connected to the polyimide film 32 via each of the adhesive films 33 (size: 15 mm × 3 mm) obtained above.

[0092] For each of the obtained resistance measurement samples 30 , the current and voltage between the copper foil 31 and the aluminum foil 34 were measured using an ammeter A and a voltmeter V, respectively, and the resistance value was calculated.

[0093] [Characteristic evaluation after cycle test]

[0094] Each of the appearance evaluation sample 20 and the resistance measurement sample 30 prepared as described above was subjected to a cycle test in which a heating cycle was repeated 250 times, wherein the heating cycle was maintained at -20°C for 30 minutes, heated to 100°C over 10 minutes, maintained at 100°C for 30 minutes, and cooled to -20°C over 10 minutes using TSA-43EL manufactured by ESPEC CORP. After the cycle test, each of the appearance evaluation sample 20 and the resistance measurement sample 30 was subjected to appearance evaluation and resistance measurement in the same manner as described above.

[0095] [Evaluation of Adhesion Strength]

[0096] Aluminum foil (size: 15 mm × 20 mm, thickness: 25 μm) was connected to copper foil (size: 40 mm × 15 mm, thickness: 25 μm) via each of the adhesive films (size: 15 mm × 3 mm) obtained above. The bonding strength of the connection was measured by a 90-degree peeling method at a peeling speed of 50 mm / min and 25° C. using Tensilon UTM-4 manufactured by Toyo Baldwin Co., Ltd. in accordance with JIS Z0237.

[0097] [Table 1]

[0098]

[0099] [Table 2]

[0100]

[0101] Explanation of symbols

[0102] 1- first electronic component, 2- second electronic component, 3- adhesive film, 4- first substrate, 5- insulating layer, 6- first electrode, 7- second substrate, 8- second electrode, 10- first conductive particle, 11- second conductive particle.

Claims

1. A method for manufacturing a connected body, comprising the step of electrically connecting a second electronic component having a second electrode to a first electronic component having a first electrode via an adhesive film, The first electronic component has a concavo-convex surface, The first electrode is disposed in a concave portion of the concave-convex surface. The second electrode is an electrode having a substantially flat surface having an area larger than that of the first electrode. The adhesive film contains: The first conductive particles are dendritic conductive particles; and The second conductive particle is a conductive particle other than the first conductive particle, and is a conductive particle having a non-conductive core and a conductive layer provided on the core. The depth of the concave portion is greater than 25 μm. The average particle size of the second conductive particles is greater than or equal to the depth of the recess. In the step, the adhesive film is disposed between the first electronic component and the second electronic component, and the second electronic component is pressure-bonded to the first electronic component such that the substantially flat surface of the second electrode is electrically connected to the first electrode.

2. The manufacturing method according to claim 1, wherein: The adhesive film has a thickness of 15 μm or more.

3. The manufacturing method according to claim 1 or 2, wherein: The thickness of the adhesive film is equal to or greater than the depth of the recess.

4. The manufacturing method according to claim 1 or 2, wherein: An average particle diameter of the second conductive particles is 2.5 times or less of a depth of the recess.

5. The manufacturing method according to claim 1 or 2, wherein: The thickness of the adhesive film is 1.2 times or more and 2 times or less of the average particle diameter of the second conductive particles.

6. Use of an adhesive film for electrical connection between a first electronic component having a first electrode and a second electronic component having a second electrode, the adhesive film comprising: The first conductive particles are dendritic conductive particles; and The second conductive particle is a conductive particle other than the first conductive particle, and is a conductive particle having a non-conductive core and a conductive layer provided on the core. The first electronic component has a concavo-convex surface, The first electrode is disposed in a concave portion of the concave-convex surface. The depth of the concave portion is greater than 25 μm. The average particle size of the second conductive particles is greater than or equal to the depth of the recess. The second electrode is an electrode having a substantially flat surface having an area larger than that of the first electrode. In the electrical connection, the substantially flat surface of the second electrode is electrically connected to the first electrode.

7. The use according to claim 6, wherein: The adhesive film has a thickness of 15 μm or more.

8. The use according to claim 6 or 7, wherein: The thickness of the adhesive film is equal to or greater than the depth of the recess.

9. The use according to claim 6 or 7, wherein: An average particle diameter of the second conductive particles is 2.5 times or less of a depth of the recess.

10. The use according to claim 6 or 7, wherein: The thickness of the adhesive film is 1.2 times or more and 2.0 times or less of the average particle diameter of the second conductive particles.

Citation Information

Patent Citations

  • Manufacturing method of connection body and anisotropic conductive adhesive

    JP2013182823A

  • Circuit connecting material and structure for connecting circuit member

    WO2009063827A1

  • Electroconductive film

    WO2014021037A1

  • Adhesive composition

    CN109642130A

  • Adhesive film

    CN110312772A